Painéis de Medium Density Fiberboard fabricados com bagaço de cana-de-açúcar e madeira de reflorestamento - Bueno, Marcus Antonio Pereira [UNESP] (2014)
The objective of this study was to analyze the potentialities of using sugarcane bagasse (SC) applied to MDF panels (Medium Density Fiberboard), along with reflorestation wood fibers (WR) of eucalyptus species, in the industry of furniture and construction. In this study, it was produced panels of MDF in four traces: 100% WR (T2), 33% SC+67% WR (T3), 67% SC+33% WR (T4) and 100% SC (T5). Also it was analyzed its physical and mechanical properties, according to the Brazilian standard NBR 15316-3 (2009). The target density of the panels was 700 kg/m, defined as medium density fiberboard. In addition it was carried out surface analysis of the top and the internal part of the panel through Scanning Electron Microscopy (SEM). The panels were bonded with urea-formaldehyde, in the proportion of 10% by mass of the panel. The results indicated that the trace with 100% SC (T5) showed the best performance among the traces, reaching, in some cases, the values recommended by NBR 15316-2 (2009). This results shows the possibility of using sugarcane bagasse for the production of MDF panels, however it is recommended more studies to improve its physical and mechanical characteristics